Aggadat Bereshit : Translated from the Hebrew with an Introduction and Notes - Teugels, Lieve, (Jewish and Christian Perspectives Series;, 2001)
Aggadat Bereshit is a homiletic Midrash on the Book of Genesis written in Hebrew, about the 10th century CE. It has a unique threefold structure, dividing the chapters or homilies according to the three parts of Tenakh : Torah (Genesis), Prophets and Writings. It contains interesting material, some unparalleled in rabbinic literature, such as an anti-Christian interpretation of Genesis 22. Besides being the first translation, this volume presents some variants from manuscripts unknown by its last editor (S. Buber, Krakow 1903). This English translation will be welcomed in the world of Jewish and Biblical Studies, academics as well as lay-persons with lesser knowledge of rabbinic Hebrew. The extensive introduction gives an up-to-date overview of the questions as to text, contents, structure, dating and provenance of this hitherto neglected Midrash.